2017
DOI: 10.3390/w9010058
|View full text |Cite
|
Sign up to set email alerts
|

SWAT Modeling for Depression-Dominated Areas: How Do Depressions Manipulate Hydrologic Modeling?

Abstract: Abstract:Modeling hydrologic processes for depression-dominated areas such as the North American Prairie Pothole Region is complex and reliant on a clear understanding of dynamic filling-spilling-merging-splitting processes of numerous depressions over the surface. Puddles are spatially distributed over a watershed and their sizes, storages, and interactions vary over time. However, most hydrologic models fail to account for these dynamic processes. Like other traditional methods, depressions are filled as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…Finally, these topographic characteristics computed for all puddle levels are used in hydrologic modeling. For example, Tahmasebi Nasab, Singh, and Chu () utilized the D‐cubed algorithm as a tool to obtain topographic details and incorporated them into the Soil and Water Assessment Tools to improve hydrologic modeling in depression‐dominated areas. For this study, surface topographic characteristics obtained from the delineation process are used to analyze dynamic connectivity and CA.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, these topographic characteristics computed for all puddle levels are used in hydrologic modeling. For example, Tahmasebi Nasab, Singh, and Chu () utilized the D‐cubed algorithm as a tool to obtain topographic details and incorporated them into the Soil and Water Assessment Tools to improve hydrologic modeling in depression‐dominated areas. For this study, surface topographic characteristics obtained from the delineation process are used to analyze dynamic connectivity and CA.…”
Section: Methodsmentioning
confidence: 99%
“…The new algorithms presented in four articles [39,40,44,45,48] provide necessary tools for better modeling effects of grazing on steppe grassland degradation, future climates on sedimentation at watershed scale, micro-topographic features (e.g., puddles) on hydrologic processes, and infiltration on the translational stability of long slopes. In addition, two articles [41,43] found that human activities were the primary reason for runoff reduction, whereas, another article [42] showed that climate variability was the dominant driver for decreasing trend of streamflow.…”
Section: Discussionmentioning
confidence: 99%
“…The articles cover a wide range of geographic regions across China [39][40][41][42][43][44]46,47,49,50] and the United States of America (USA) [45,48] with contrasting hydro-climate, soil, and vegetation conditions. Thus, the results presented in these articles can have global inferences: the data, analysis/modeling approaches, results, and findings will lay a solid foundation to further our scientific understanding of water-soil-vegetation interactions, ultimately leading to the development of practically effective solutions to sustaining the globe's ecosystem health and productivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations